Earthquakes in Javanese theological interpretation: The study of Serat Primbon manuscripts from the Yogyakarta Sultanate Palace - Islah Gusmian (Center for Science and Technology, IAIN Surakarta, 2019)
This article examined the Javanese view on the earthquakes recorded in the manuscripts. Javanese people were chosen because they have a typical and unique view in interacting with fellow humans, nature and God. While the manuscripts were placed as a database, because it is a historical record, thoughts, attitudes, views in the past. There are three problems examined in this article, namely: how are the understanding and attitudes of the Javanese people towards earthquake events, what are the factors influencing that understanding, and what are the functions in disaster mitigation? By using Karl Mannheim's sociological theory of knowledge, it was found that Javanese people understand earthquakes as a sign system attached to predictive and subjective-imaginative meanings and spiritually responded to by prayer and slametan ceremonies. And the most important thing found in this study is that the Javanese understand the earthquakes actively and positively, in which they always move from one destiny to another to maintain harmony and safety.